2017
DOI: 10.1111/1440-1681.12870
|View full text |Cite
|
Sign up to set email alerts
|

Epac‐induced ryanodine receptor type 2 activation inhibits sodium currents in atrial and ventricular murine cardiomyocytes

Abstract: SummaryAcute RyR2 activation by exchange protein directly activated by cAMP (Epac) reversibly perturbs myocyte Ca2+ homeostasis, slows myocardial action potential conduction, and exerts pro‐arrhythmic effects. Loose patch‐clamp studies, preserving in vivo extracellular and intracellular conditions, investigated Na+ current in intact cardiomyocytes in murine atrial and ventricular preparations following Epac activation. Depolarising steps to varying test voltages activated typical voltage‐dependent Na+ currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Thus Ca 2+ could directly bind to EF-hand intracellular motifs in Na V 1.5, bind with EF-hand motifs on Ca 2+ -calmodulin (CaM) that in turn reacts with IQ sites on Na V 1.5, or bind to CaM-dependent kinase II (CaMKII) activating its phosphorylating, inhibitory action on Na V 1.5 [59,60]. Finally, recent reports demonstrated that both genetic modifications in RyR2 [59] and acute activation of protein kinase A (PKA)-independent exchange protein increase ryanodine receptor mediated sarcoplasmic reticular Ca 2+ release [61] with reversible Na + channel effects [62]. Similarly, altered Ca 2+ homoeostasis elevating cytosolic [Ca 2+ ] leads to gap junction closure reducing intercellular coupling [63–65].…”
Section: Discussionmentioning
confidence: 99%
“…Thus Ca 2+ could directly bind to EF-hand intracellular motifs in Na V 1.5, bind with EF-hand motifs on Ca 2+ -calmodulin (CaM) that in turn reacts with IQ sites on Na V 1.5, or bind to CaM-dependent kinase II (CaMKII) activating its phosphorylating, inhibitory action on Na V 1.5 [59,60]. Finally, recent reports demonstrated that both genetic modifications in RyR2 [59] and acute activation of protein kinase A (PKA)-independent exchange protein increase ryanodine receptor mediated sarcoplasmic reticular Ca 2+ release [61] with reversible Na + channel effects [62]. Similarly, altered Ca 2+ homoeostasis elevating cytosolic [Ca 2+ ] leads to gap junction closure reducing intercellular coupling [63–65].…”
Section: Discussionmentioning
confidence: 99%
“…Three hearts were studied from each group. The mice studied were littermates of animals whose hearts had undergone electrophysiological study reported elsewhere (Valli et al, 2017a,b, 2018a,b). Young mice were between the ages of 12–16 weeks old and aged mice greater than 52 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Dantrolene itself contrastingly produced increases in I Na . Murine cardiac muscle showed concordant effects of enhanced SR Ca 2+ release either with 8-CPT application 11 or in RyR2-P2328S genetic variants 12 .…”
Section: Introductionmentioning
confidence: 98%